Strategies to Improve The Performance of Private University Employees in South Tangerang with Importance Performance Analysis - Annuridya Rosyidta Pratiwi Octasylva; Sarita Pemana; Afina Putri Vindiana (Universitas Veteran Bangun Nusantara, 2025)
Private Universities (PTS) play an important role in the provision of competitive higher education services, but face challenges in ensuring that the performance of human resources (HR) remains optimal to meet the demands of service quality, accreditation, and stakeholder expectations. The main problem that arises is the gap between the performance attributes that employees consider important and the actual perceived performance, which has an impact on motivation, work effectiveness, and institutional competitiveness. This study aims to diagnose employee performance attributes at PTS by focusing on identifying priority attributes, measuring the gap between the level of importance and performance, and formulating performance improvement strategies that can be implemented practically by management. The method used is Importance–Performance Analysis (IPA) with 20 attributes that are evaluated through two dimensions: importance and performance. The results showed that the attribute of reward for work performance (MT4) was in Quadrant I, indicating high importance but low performance so that it required immediate intervention. Meanwhile, the attributes of leadership, discipline, and communication are in Quadrant II as organizational strengths that need to be maintained. These findings indicate the need to strengthen the reward system, leadership appreciation practices, and motivation strategies based on recognition and development. In conclusion, IPA is able to provide an evidence-based overview of priorities that help private universities effectively allocate resources to improve human resource performance and strengthen institutional competitive advantage.